Advances in identifying GM plants: toward the routine detection of 'hidden' and 'new' GMOs - Bertheau, Yves (Burleigh Dodds Series in Agricultural Science, 2021)
In 2018 the Court of Justice of the European Union recalled that organisms with genomes modified by artifactual techniques should be considered GMOs under European regulations. GMOs derived from cultures of cells isolated in vitro or from new genomic techniques must therefore be traceable. This chapter reviews the various technical steps and characteristics of those techniques causing genomic and epigenomic scars and signatures. These intentional and unintentional traces, some of which are already used for varietal identification, and are being standardized, can be used to identify these GMOs and differentiate them from natural mutants. The chapter suggests a routine procedure for operators and control laboratories to achieve this without additional costs.